Pelatihan Tari Kreasi sebagai Bentuk Apresiasi Seni di SD Negeri F. 1 Trikoyo Kabupaten Musi Rawas - Andriana Sofiarini; Ratna Wulan Sari (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
Art education is a form of education that provides opportunities for children to appreciate themselves and their surroundings. A sense of appreciation can emerge if learning is implemented well and correctly by educators in schools. This means that educators can help students achieve the desired level of appreciation. Educators are expected to have appropriate competencies in the arts, especially dance. However, in practice, the use of dance does not always achieve the desired goal. Many students are not aware of the appreciation of dance. They also tend to think dance is not that important. Some of them do not even know what are the purposes and benefits of dancing. Therefore, dance training is needed for students, so that they better understand the meaning of dance appreciation. The method used in creative dance training includes preparation, analysis of dance training design, implementation, and evaluation. As a result, students can apply the dance that has been taught. The students were able to present the dance at an art performance event held on Wednesday, February 26, 2025. The purpose of the dance training is to introduce and preserve works of art, including dance in Indonesia. In addition, this training aims to increase appreciation for dance and enrich students' knowledge of dance culture in the archipelago.